Analisis Efisiensi Pemasaran Cabai Merah di Kabupaten Batubara - Nurhidayana Nurhidayana; Retna Astuti Kuswardani; M. Akbar Siregar (JURNAL AGRICA, 2018)
The red chili commodities is the important contribution in farming, but the nature of this perishable commodity, is seasonal, while consumption occurs throughout the year, it requires a good marketing system. The objectives of this study to get a current red chili marketing system at the Batubara District and analyze the most efficient marketing system and analyze the margin of red chilli marketing at the Batubara District. The methode of study is descriptive quantitative by questionnaire. Respondents consisted of 26 farmers producers, collector of 26, merchant retailers of 18.  The result of studies shows that : 1) the marketing channel 3 has the lowest marketing margin of Rp. 4500, 2) smaller marketing margins obtained from the small price difference between farm gate price and the retail price level (consumer price). This shows the marketing channel 3 is more efficient than marketing channels 1, 2 and 4 . However, based to the amount of red chili farmers who choose to use channel 3 is lower than channels 1 and 2 . So operationally channel 3 is not necessarily more efficient because it is only used by 18.57 % of the farmers while channel 1 at 42.85, and channel 2 at 25.71 %. The role of stakeholders to improve the income of farmers through efficient marketing channels is needed. Government efforts are needed to increase their knowledge of processing technologies in the long term so that farmers are able to cultivate chili production in the form of home industry Keywords : efficiency, marketing, chili